2017
DOI: 10.1371/journal.pone.0176955
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Saccharomyces cerevisiae in psoriasis patients, restored by Dimethylfumarate therapy (DMF)

Abstract: BackgroundPsoriasis and inflammatory bowel disease (IBD) are chronic inflammatory diseases sharing similar pathogenic pathways. Intestinal microbial changes such as a decrease of bakers’ yeast Saccharomyces cerevisiae have been reported in IBD, suggesting the presence of a gut-skin axis.ObjectiveTo investigate whether the S. cerevisiae abundance was altered in psoriasis patients versus healthy controls, and whether dimethylfumarate (DMF) interacted with this yeast.MethodsUsing qPCR, faecal samples were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Metallo-aminopeptidases are etiological factors of microbial infections, for example, meningitis caused by Neisseria meningitides, or yeast species. Accordingly, Saccharomyces cerevisiae can cause alterations in the production of B4 leukotriene and is a target in the treatment of bowel diseases, candidiasis, or psoriasis [94]. The full description of the active centers and substrate specificities of some microbial metallo-aminopeptidases is not always possible because of the lack of exhaustive data (Table 6).…”
Section: Aminopeptidases From Pathogenic Bacteriamentioning
confidence: 99%
“…Metallo-aminopeptidases are etiological factors of microbial infections, for example, meningitis caused by Neisseria meningitides, or yeast species. Accordingly, Saccharomyces cerevisiae can cause alterations in the production of B4 leukotriene and is a target in the treatment of bowel diseases, candidiasis, or psoriasis [94]. The full description of the active centers and substrate specificities of some microbial metallo-aminopeptidases is not always possible because of the lack of exhaustive data (Table 6).…”
Section: Aminopeptidases From Pathogenic Bacteriamentioning
confidence: 99%
“…As S. cerevisiae is known to have beneficial immunomodulatory properties, this may offer a previously uninvestigated means by which DMF elicits its anti-psoriatic effects, i.e. via restoration of an anti-inflammatory microbiome [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…50 In addition, faecal Saccharomyces cerevisiae abundance is decreased in patients with psoriasis compared with healthy controls. 51 Primary sclerosing cholangitis has also been associated with decreased faecal microbial diversity. 15,52 One study has suggested that IBD patients have similar dysbiosis to IBD-PSC patients.…”
Section: Dysbiosis and Gut Microbiotamentioning
confidence: 99%